Association of Intellectual Risk Taking with Science Achievement of Gifted Students and Comparison of their Intellectual Risk Taking in Different Grades and Gender - Köksal, Mustafa Serdar; Firat, Esra Açikgül; Akkaya, Gamze (Journal of the American Academy of Special Education Professionals, 2021)
This study explores the association between intellectual risk taking and science achievement of gifted students and difference in grade levels and gender. The participants were 122 sixth, seventh and eighth grade gifted students in Turkey. In data collection, "science achievement test" and "intellectual risk taking scale in learning science" were utilized. For analyzing data, nonparametric tests (Spearman correlation, Mann-Whitney U and Kruskal Wallis) were used. The findings revealed that while there were no significant difference in gender, and the relationship between risk taking and science achievement was not statistically significant, the study determined significance in the difference between grade levels. A significant decrease in eighth grade was observed. This study warns about clear decline in eight grade in terms of intellectual risk taking and about active participation to learning.